Holocene climatic change in Morocco: a quantitative reconstruction from pollen data - Cheddadi, R; Lamb, H F; Guiot, J; van der Kaars, S (Climate Dynamics, 1998)
Annual precipitation, July and January tem- peratures were reconstructed from a continuous Holo- cene pollen sequence from the Middle Atlas, Morocco, using the best modern analogues method. The recon- structions show a clear difference between the early and late Holocene: from &10 ka to &6.5 ka the climate was drier and warmer than during the period since 6.5 ka. The average value of annual precipitation was &870mm until 6.5 ka, then rose to &940 mm. Be- tween 10 ka and 6.5 ka January and July temperatures were about 4 °C higher than the present. Both temper- atures show a marked decrease between 7 ka and 6 ka. After 6.5 ka July and January temperatures fluctuated between 21 and 23 °C, and 2.5 and 5 °C respectively. January temperatures show a period of intermediate values (&3.5 °C) between 4 ka and 5.5 ka. The recon- structed climate values generally match palaeolim- nological data from the same core, which show five intervals of low lake level during the Holocene. They are also consistent with regional-scale COHMAP simulated palaeoclimate that shows contrasting pat- terns of rainfall variation between the northwester- nmost part of Africa and the intertropical band
APS
Keywords: climate; Holocene; Morocco; paleoclimate; pollen

Vegetational response to holocene climatic change: Pollen and palaeolimnological data from the Middle Atlas, Morocco - Lamb, H F; VanderKaars, S (HOLOCENE, 1995)
Pollen data from a radiocarbon-dated lake-sediment core from the Middle Atlas of Morocco show that forests of evergreen and winter-deciduous oaks (Quercus rotundifolia, Q. canariensis), present from the start of the Holocene, were invaded at 6200 BP by Cedrus atlantica in low numbers. Two thousand years later, after a short period characterized by higher deciduous oak frequency, Cedrus increased to its present abundance. These changes may have been in response to increasing effective moisture as summer temperatures decreased with declining northern-hemisphere seasonality, under the influence of precessional forcing. Palaeolimnological data from the same core show that the lake level fell sharply in five 200-400 yr-long and intervals, but the pollen data show little or no evidence of a vegetational response. This suggests that summer (growing-season) rainfall remained adequate during the dry intervals, whereas depletion of the groundwater aquifer was the result of reduced winter precipitation. Anthropogenic exploitation since c. 1300 BP has had a greater effect on the forest ecosystem than any of the Holocene and intervals.
Keywords: climatic change; Environment; Palaeolimnology; pollen